2020
DOI: 10.3390/v12040397
|View full text |Cite
|
Sign up to set email alerts
|

High Transmission Potential of West Nile Virus Lineage 1 for Cx. pipiens s.l. of Iran

Abstract: Vector competence is an important parameter in evaluating whether a species plays a role in transmission of an arbovirus. Although the protocols are similar, interpretation of results is unique given the specific interactions that exist between a mosquito population and a viral genotype. Here, we assessed the infection (IR), dissemination (DR), and transmission (TR) rates of Cx. pipiens s.l., collected from Iran, for West Nile virus (WNV) lineage 1a. We showed that Cx. pipiens s.l. mosquitoes in Iran were susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…In our study, saliva samples from the 14th pi were not positive in any of the tests performed, being possible to identify and quantify the viral load only in the samples of 21rst pi, with titers ranging from 2x10 2 to 4x10 2 PFU/mL, values that are high when analyzing saliva in isolation, but when evaluating the saliva samples together with the head and body samples belonging to the same pi, a reduction in the viral load in the saliva is observed. These data are similar to those identi ed by Bakhshi et al [41] in research with Cx. pipiens, where it was observed that despite the presence of WNV in saliva after 21 days after infection, the viral titer is lower than that observed in body and head samples belonging to the same group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, saliva samples from the 14th pi were not positive in any of the tests performed, being possible to identify and quantify the viral load only in the samples of 21rst pi, with titers ranging from 2x10 2 to 4x10 2 PFU/mL, values that are high when analyzing saliva in isolation, but when evaluating the saliva samples together with the head and body samples belonging to the same pi, a reduction in the viral load in the saliva is observed. These data are similar to those identi ed by Bakhshi et al [41] in research with Cx. pipiens, where it was observed that despite the presence of WNV in saliva after 21 days after infection, the viral titer is lower than that observed in body and head samples belonging to the same group.…”
Section: Discussionsupporting
confidence: 92%
“…It was observed that the studied population has high susceptibility to the WNV strain used, since the virus was identi ed in all body samples of 7th, 14th and 21rst pi, as well as it was possible to quantify the viral titer in the same samples in the same period, corroborating with data presented by Bakhshi et al [41] which demonstrates that Cx. pipiens species also showed high susceptibility to WNV strain belonging to 1a lineage isolated in Iran, with infection rates varying from 70% to 88% at 7th and 21rst pi.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Clade 1a is globally spread, clade 1b, or Kunjin virus (KUNV), mainly circulates in Australia, and clade 1c (now reassigned to Lin 5) has only been described in India [ 34 ]. Lin 2 has been reported in Africa, Europe, and the Middle East [ 35 ]. Lin 3, or Rabensburg virus, Lin 4, and a putative Lin 6 (closely related to Lin 4) were described in Czech Republic, Russia, and Spain, respectively [ 33 ].…”
Section: Molecular Classificationmentioning
confidence: 99%